Outcomes for Community-Acquired Extended-Spectrum Beta-Lactamase (ESBL) Escherichia coli Urinary Tract Infections (UTIs) in Children Treated With Empiric Noncarbapenem Antibiotic Therapy. (October 2020) - Holmen, Jenna
Abstract : Background: Empiric therapy with a cephalosporin antibiotic is the current standard of care for children with urinary tract infections (UTIs). However, as the rate of UTI due to extended-spectrum β-lactamase (ESBL)–producing organisms rises, there is concern that treatment failures may increase. Carbapenems are the most reliable antimicrobials for treating ESBL organisms, but empiric coverage with carbapenems necessitates hospitalization for intravenous therapy. Objective: We evaluated whether empiric noncarbapenem therapy in patients with ESBL Escherichia coli UTI is associated with poorer outcomes. Methods: We conducted a case-control study of patients with UTIs treated with empiric penicillin- or cephalosporin-based antibiotics from January 1, 2017, to December 31, 2018. We compared outcomes in cases with ESBL E. coli UTI with age-matched controls with a cephalosporin-susceptible E. coli UTI. Logistic regression was used to compare the odds of clinical failure (persistent symptoms and/or fever) at 48–72 hours. We further evaluated the odds of hospitalization and UTI recurrence between groups. Results: Of the 228 enrolled patients, 51 were cases and 177 controls. Cases were more likely to have underlying medical conditions (45% vs 21%). The odd ratio of clinical failure at 48–72 hours after initiation for cases compared to controls was 4.83 (95% CI, 0.94–24.92; P = .06). These odds were was not influenced by age, presence of an underlying medical condition, or fever. The overall adjusted odd ratio of hospitalization for cases compared to controls was 12.09 (95% CI, 0.995–4.38, P = .052). Most patients admitted at presentation had an underlying medical condition (30 of 64, 47%) and/or fever (54 of 64, 84%). Among 30 cases initially managed as outpatients, only 2 (7%) were later admitted due to clinical failure. There was no difference in the likelihood of UTI recurrence within 60 days for the 2 groups (adjusted OR, 1.34; 95% CI, 0.47–3.78; P = .58). Conclusions: At 48–72 hours, there was no significant difference in the odds of clinical failure for patients with ESBL E. coli UTI compared to patients with non-ESBL E. coli UTI receiving empiric noncarbapenem therapy. Although we detected a trend toward a higher odds of hospitalization among cases, this result was largely due to a higher clinical complexity among cases at baseline. Only 2 cases required admission for failure of outpatient therapy. There was no increased risk of UTI recurrence among cases. This study suggests that initial discordant antibiotic therapy may not increase the risk of a poor outcome in children with ESBL E. coli UTI. Funding: None Disclosures: None